2020
DOI: 10.1155/2020/1273198
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Adiponectin-Transfected Endothelial Progenitor Cells on Cognitive Function in D-Galactose-Induced Aging Rats

Abstract: Aging is a multifactorial process involving the cumulative effects of inflammation, oxidative stress, and mitochondrial dynamics, which can produce complex structural and biochemical alterations to the nervous system and lead to dysfunction of microcirculation, blood-brain barrier (BBB), and other problems in the brain. Long-term injection of D-galactose (D-gal) can induce chronic inflammation and oxidative stress, accelerating aging. The model of accelerated aging with long-term administration of D-gal have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Research has confirms that H 2 S possesses essential functions in antagonizing cognitive impairment (J. Huang et al, 2020 ; Rizzo et al, 2020 ). Recently, our study has also proved that H 2 S also attenuates CRS-induced cognitive impairment ( Xiao-Na et al, 2017 ), but the potential mechanism contributes to this process remains poorly understood.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Research has confirms that H 2 S possesses essential functions in antagonizing cognitive impairment (J. Huang et al, 2020 ; Rizzo et al, 2020 ). Recently, our study has also proved that H 2 S also attenuates CRS-induced cognitive impairment ( Xiao-Na et al, 2017 ), but the potential mechanism contributes to this process remains poorly understood.…”
Section: Discussionmentioning
confidence: 96%
“…A growing number of studies have showed that adiponectin can promote cognitive function (J. Huang et al, 2020 ; Rizzo et al, 2020 ). Notably, we have previously found that NaHS (a donor of H 2 S) increases the level of adiponectin in the hippocampus of CRS-exposed rats ( Ashish et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mice of accelerated senescence with the intake of d-gal have been extensive used in anti-aging research, due to the rise of oxidative pressure and decrease of cognition that similarity to natural senescence in the creatures (Huang et al, 2020). Mice treated with d-gal exhibited outcomes similar to those observed in natural aging in mice (Uddin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…And APN-transfected EPC have a beneficial effect on cognitive function in D-gal-induced aging rats. Besides, BBB dysfunction and angiogenesis were also improved, and neuroinflammation and apoptosis rate were reduced [ 26 ].…”
Section: Discussionmentioning
confidence: 99%